La Extremadura de Alonso Zamora Vicente - Viudas Camarasa, Antonio (Revista de Filología Románica, 2008)
This article proposes a portrait of Alonso Zamora Vicente through his relationship with the Spanish region of Extremadura, whose culture and arts he contributed largely to spread worldwide.